Utilization of poetry in teaching Turkish to Kyrgyz at c1 level in emphasis and pronunciation - Barcın, Sibel (Frontiers in Education, 2024)
The aim of this study is to use poetry as an effective tool to improve students’ language skills in teaching Turkish to Kyrgyz. In this context, the teaching of emphasis and pronunciation through poetry is emphasized. In this study, action research, one of the qualitative research methods, was used. The study group of the research consists of 10 Kyrgyz students studying at Kyrgyzstan-Turkey Manas University School of Foreign Languages in the academic year 2022–2023 and who voluntarily participated in the study. Based on this information, students were recommended Necip Fazıl Kısakürek’s poem “Kaldırımlar,” Atillâ İlhan’s poem “Ben Sana Mecburum” and Yavuz Bülent Bâkiler’s poem “Şaşırdım Kaldım İşte” on the first day of the study. Students read the poem of their choice and then prepared for it for 4 days. On the 5th day, they read the poem in the classroom. The data obtained during reading were written down and a comparison was made by considering emphasis, intonation and pronunciation. The data were categorized as “errors related to the mispronunciation of /h/ and /k/ sounds,” “errors related to emphasis” and “ignoring the rhythmic element” and themes were formed and students’ mispronunciations were presented in tables. As a result of the comparisons, the differences between the first day and the last day were evaluated. The findings were interpreted by comparing them with the studies in the literature.